PENGARUH KOMPETENSI, MOTIVASI, DAN DUKUNGAN SOSIAL TERHADAP NIAT BERWIRAUSAHA MAHASISWA - Subroto, Agus Andi (Penerbit Lafadz Jaya, 2025)
The purpose of this study is to evaluate how competence, motivation, and social support impact the entrepreneurial intention of students who participate in the Management study program. The background of this research is based on the importance of understanding the components that encourage students to be entrepreneurial in the midst of economic challenges and increasingly fierce job competition. A quantitative method was used to collect data, with questionnaires distributed to 53 respondents. Validity, reliability, and multiple linear regression tests were performed on the data for analysis. The results of the study show that three independent variables of competence, motivation, and social support have a significant effect on entrepreneurial intention. Motivation, among the three, is the factor that most influences the desire of students to start a business. These three variables can account for 62.1% of the variation in entrepreneurial intention, according to the determination coefficient value (R2) of 0.621. These results are in line with the Theory of Planned Behavior, which says that attitudes, subjective norms, and perceived control of behavior affect intention. The development of entrepreneurial education policies that focus on good competencies, great encouragement, and a supportive social environment is part of this research.